STRATEGI OPTIMALISASI KINERJA BANK SYARIAH: PENDEKATAN TINJAUAN LITERATUR: Optimization Strategy of Syariah Bank Performance: A Literature Review Approach - Ahmad Sumiyanto (Yayasan Pendidikan Tanggui Baimbaian, 2025)
The more rapid technological development in Indonesia advances, the more changes will have an impact on people's lives, one of which is in agreements with electronic seals or what are called e-seals. However, in its current application electronic seals are little known by the public and only certain people can know about them. In this case, the general public is also less confident about the validity of electronic seals because they are considered to be able to be faked. In collecting data in this research, this type of normative legal research is used, namely by collecting data sources from literature materials. The results of the analysis obtained in this research are that a document on which an electronic seal is placed also has validity, because the government has issued an electronic seal which of course is valid in the eyes of the law.